2009
DOI: 10.1111/j.1468-2982.2009.02014.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin provocation in normal subjects is not a useful human migraine model?

Abstract: Provoking delayed migraine with nitroglycerin in migraine sufferers is a cumbersome model. Patients are difficult to recruit, migraine comes on late and variably and only 50-80% of patients develop an attack. A model using normal volunteers would be much more useful, but it should be validated by testing the response to drugs of known efficacy in acute migraine. Furthermore, treatment during headache rather than pretreatment is the most naturalist method. To fulfil these requirements we used continuous long-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…Previous studies have shown that neither zolmitriptan nor aspirin, nor olcegepant, have an effect on headache induced by long-lasting glyceryl trinitrate (GTN) infusion (17,18). The present results are in agreement as 5-ISMN releases NO continuously over many hours and we saw no effect of sumatriptan.…”
Section: Pathophysiological Implicationssupporting
confidence: 91%
“…Previous studies have shown that neither zolmitriptan nor aspirin, nor olcegepant, have an effect on headache induced by long-lasting glyceryl trinitrate (GTN) infusion (17,18). The present results are in agreement as 5-ISMN releases NO continuously over many hours and we saw no effect of sumatriptan.…”
Section: Pathophysiological Implicationssupporting
confidence: 91%
“…In particular, FHM-1 patients are not hypersensitive to CGRP [47] and nitric oxide [48], by contrast with patients with migraine with or without aura [49]. Since administration of CGRP or of a nitric oxide donor does not induce migraine in healthy subjects [50] it is likely that the hypersensitivity of migraineurs to these substances implies abnormal signaling downstream of the primary mechanism of CGRP and nitric oxide activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore understandable that some studies resolve to investigating pharmacologically provoked migraine like headache or try to trigger attacks using natural stimuli . Both approaches are problematic: at the moment we do not know whether the migraine like headache experienced by migraine patients following NO‐ or pituitary adenylate cyclase activating peptide (PACAP)‐administration is pathophysiologically identical to spontaneous migraine attacks . A crucial point in imaging studies using pharmacological induction of headaches is to separate the headache‐specific signal changes, ie, the condition of interest, from general drug effects.…”
Section: Imaging Migraine Attacksmentioning
confidence: 99%
“…5,12,[24][25][26][27][28] Both approaches are problematic: at the moment we do not know whether the migraine like headache experienced by migraine patients following NO 29,30 -or pituitary adenylate cyclase activating peptide (PACAP) 31 -administration is pathophysiologically identical to spontaneous migraine attacks. [32][33][34][35][36][37] A crucial point in imaging studies using pharmacological induction of headaches is to separate the headachespecific signal changes, ie, the condition of interest, from general drug effects. It is thus necessary during piloting to exclude any such changes or, if they exist, to control them via an apt control group.…”
Section: Imaging Migraine Attacksmentioning
confidence: 99%